1940
DOI: 10.1021/ie50364a026
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Boiling Points of Aliphatic Hydrocarbons

Abstract: The boiling points of the aliphatic hydrocarbons of any known type may be calculated readily from their molecular boiling point numbers by means of the boiling point equation. The molecular boiling point number of the molecule is obtained by summing up the boiling point numbers representing the various atoms and structural groupings in the molecule. THE calculation of the boiling points of the aliphatic hydrocarbons may be accomplished by the use of the boiling point equation developed previously (1). The meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1943
1943
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…The value of the boiling point number is determined by the aromatic ring structures and side chains of the molecules. For the compounds containing a monoaromatic structure and n -alkyl side chain, there exists a relationship described in empirical formula where N b,n is the boiling point number of the molecule with a n -alkyl side chain, N b,0 is the boiling point number of the monoaromatic ring without any side chains, and n is the carbon number of the side chain.…”
Section: Resultsmentioning
confidence: 99%
“…The value of the boiling point number is determined by the aromatic ring structures and side chains of the molecules. For the compounds containing a monoaromatic structure and n -alkyl side chain, there exists a relationship described in empirical formula where N b,n is the boiling point number of the molecule with a n -alkyl side chain, N b,0 is the boiling point number of the monoaromatic ring without any side chains, and n is the carbon number of the side chain.…”
Section: Resultsmentioning
confidence: 99%
“…It is seen that there is a reasonably good linear relationship represented by the equation S = 0.118 + 0.878C, where S is the density of a silicon compound and C is that of its carbon analog. Lewis and Newkirk (123) have shown that an additive system of atomic and group boiling-point numbers developed by Kinney (101)(102)(103)(104)(105) for carbon compounds can be extended to organosilicon compounds. This suggests that a linear relationship like that for densities should apply to the boiling points of silicon and carbon analogs, and such is found to be the case.…”
Section: A Density and Boiling Pointmentioning
confidence: 99%
“…Our initial investigation of the relationship between Y BP values and molecular structure was carried out with acyclic alkanes (this work was based on an early report by Kinney,4 who introduced the concept of a boiling point number, Y, as a measure of T B values). Their Y BP values could be predicted quite accurately from molecular structure, as is shown in equation 2.…”
Section: Introductionmentioning
confidence: 99%